Multidisciplinary Cooperation By Students In A European University Of Applied Sciences - kamphorst, jan (Journal of University Teaching and Learning Practice, 2018)
Today, multidisciplinary cooperation is an important objective of higher vocational education in Europe as well as other countries. The aim of this study was to explore how, and to what extent, fourth year bachelor students from different domains cooperate in multidisciplinary teams at two research centers. Data for 71 students were collected with a semi-structured questionnaire, followed by focus group discussions in 14 groups. Results indicated that students accomplished multidisciplinary cooperation to varying degrees, depending on differences in disciplinary program backgrounds, student characteristics, the research center, the thematic group they belonged to, and the quality of the ‘graduation research assignment’. For example, students experienced pressure from their training college to conduct their research autonomously, and this affected the degree to which the goal of multidisciplinary cooperation was reached during the final assignment before graduation. The results of this study were useful for improvement of the professional learning environment in which training colleges and research centers cooperate.